2-keto-3-deoxygluconate transport system in Erwinia chrysanthemi. - Condemine, G (1987)
In Erwinia chrysanthemi, the gene kdgT encodes a transport system responsible for the uptake of ketodeoxyuronates. We studied the biochemical properties of this transport system. The bacteria could grow on 2,5-diketo-3-deoxygluconate but not on 2-keto-3-deoxygluconate. The 2-keto-3-deoxygluconate entry reaction displayed saturation kinetics, with an apparent Km of 0.52 mM (at 30 degrees C and pH 7). 5-Keto-4-deoxyuronate and 2,5-diketo-3-deoxygluconate appeared to be competitive inhibitors, with Kis of 0.11 and 0.06 mM, respectively. The 2-keto-3-deoxygluconate permease could mediate the uptake of glucuronate with a low affinity. kdgT was cloned on an R-prime plasmid formed by in vivo complementation of a kdgT mutation of Escherichia coli. After being subcloned, it was mutagenized with a mini-Mu-lac transposable element able to form fusions with the lacZ gene. We introduced a kdgT-lac fusion into the E. chrysanthemi chromosome by marker exchange recombination and studied its regulation. kdgT product synthesis was not induced by external 2-keto-3-deoxygluconate in the wild-type strain but was induced by galacturonate and polygalacturonate. Two types of regulatory mutants able to grow on 2-keto-3-deoxygluconate as the sole carbon source were studied. Mutants of one group had a mutation in the operator region of kdgT; mutants of the other group had a mutation in kdgR, a regulatory gene controlling kdgT expression.